2016
DOI: 10.1038/nature18606
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of accessible chromatin in mammalian preimplantation embryos

Abstract: In mammals, extensive chromatin reorganization is essential for reprogramming terminally committed gametes to a totipotent state during preimplantation development. However, the global chromatin landscape and its dynamics in this period remain unexplored. Here we report a genome-wide map of accessible chromatin in mouse preimplantation embryos using an improved assay for transposase-accessible chromatin with high throughput sequencing (ATAC-seq) approach with CRISPR/Cas9-assisted mitochondrial DNA depletion. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

46
584
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 606 publications
(667 citation statements)
references
References 50 publications
46
584
1
Order By: Relevance
“…It has been shown that NR5A2 binds directly to both promoter and enhancer regions in Pou5f1 and activates its expression (128). Nr5a2 is highly expressed during development and the knockdown of Nr5a2 in zygote leads to downregulation of Pou5f1 expression (24). In our previous work we showed that mice exposed to ATZ have a higher number of H3K4me3 peaks that contain Nr5a2 motif (42).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that NR5A2 binds directly to both promoter and enhancer regions in Pou5f1 and activates its expression (128). Nr5a2 is highly expressed during development and the knockdown of Nr5a2 in zygote leads to downregulation of Pou5f1 expression (24). In our previous work we showed that mice exposed to ATZ have a higher number of H3K4me3 peaks that contain Nr5a2 motif (42).…”
Section: Discussionmentioning
confidence: 99%
“…Our model predicts that the changes in germ cells induced by ATZ will be preserved at limited genomic regions. Specifically, we propose that the genes, which are expressed from both paternal and maternal alleles in the very early zygote (such as Pou5f1, Nr5a2, Klf2 ) are required to be in an open chromatin state (24) that likely preserves their histones as well as the histone modifications. Other potential candidates to mediate ATZ effects are ATP-binding proteins, since human sperm nucleosome fraction of genome is enriched in genes encoding them (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations